The Inverse Relationship Between Cancer and Alzheimer's Disease: A Possible Mechanism - W. Nixon, Daniel (Current Alzheimer Research, 2017)
Background: Cancer and Alzheimer's disease (AD) are both associated with aging, but do not often occur together. Obesity is a shared risk factor for both diseases and may be involved in this curious clinical observation. Fat cells produce many active substances, including leptin and adiponectin; leptin has cancer stimulating and AD inhibiting properties, while adiponectin can inhibit cancer but stimulate AD. Objective: To describe the opposing effects of leptin and adiponectin on cancer and AD, to outline signaling pathways involved in these effects and to suggest new research on effective control strategies for both diseases. Methods: A review was conducted to document the inverse cancer/AD relationship and the role of excess body fat as a common risk factor. Previous studies have suggested the involvement of p53, Wnt and other cell signaling pathways in this inverse relationship. The opposing effects of leptin and adiponectin on these signaling pathways in cancer and AD were evaluated. Results: The inverse cancer/AD relationship is well documented, as is the role of excess body fat, especially central obesity, in increasing risk for both diseases. Leptin and adiponectin have opposing effects in cancer and AD mediated by signaling factors that influence apoptosis, angiogenesis, and other cell growth controls. Wnt and p53 are prominent among these signaling factors. Conclusion: Opposing effects of leptin and adiponectin, mediated by specific cell signaling pathways, are involved in the inverse cancer/Ad relationship. Future research aimed at modifying the leptin/adiponectin ratio may lead to important treatment and control approaches in both cancer and AD.
Keywords: Wnt